Geographic variation in aggressive signalling behaviour of the Jacky dragon - Barquero Arroyo, Marco David (2015)
Signal diversification is often the product of sexual and/or natural selection and may be accompanied by genetic differentiation or simply reflect a plastic response to social and environmental variables.We use an agamid lizard endemic to Australia, the Jacky dragon (Amphibolurus muricatus), to examine the relationships between population relatedness, morphology and signalling behaviour. We also tested whether males are able to discriminate among rivals from different populations and whether they respond more aggressively to more closely related populations. We studied three populations, two of which belong to the same genetic clade. Individuals from the two most closely related populations were also more similar in morphology than lizards from the third, more distant, population. However, all three populations differed in characteristics of their signalling behaviour including latency to display and the interval between displays. In addition, animals from all populations showed similar levels of aggression when matched with individuals from the same or different populations in staged trials and thus did not show evidence of population-level discrimination. We argue that display variation might be a consequence of behavioural plasticity and that, despite difference in genetic structure, morphology and behaviour, this species retains a cohesive communication system.